Evolution of Salvia key enzyme genes based on metabolomic and transcriptomic insights into mitochondrial quality control - Zhenyu Zhao; Huijie Li; Boyao Wang; Xuhao Gong; Jinhua Gu (KeAi Communications Co., Ltd., 2024)
The purpose of this study was to explore the relationship between the evolution of key Salvia enzyme genes and metabolite biological activity on mitochondrial quality control. Metabolomics and transcriptomics were performed to detect the metabolites of Salvia and 76AH1 (CYP450) genes and a maximum likelihood tree for Salvia was established. Additionally, the protein properties of 76AH were analyzed and the metabolite, as well as mitochondrial quality control, targets were downloaded from the TCMSP, BATMAN, and GeneCards databases and analyzed. Molecular docking of PINK1 with cryptotanshinone and tanshinone IIA was assessed and a molecular binding area was identified. Moreover, the specific types of Salvia secondary metabolites were accurately identified and quantified with nearly all AH1 genes having been sequenced. This study begins to elucidate the relationship between species evolution and biological activity. Specifically, the structural analysis demonstrates that cryptotanshinone and tanshinone IIA exhibit strong pharmacological activity in mitochondrial quality control.